先化简,再求值:[(x²-2x+1)分之x]÷[(x²-1)分之(x+1)+1],其中x=根号2+1

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 04:53:18
先化简,再求值:[(x²-2x+1)分之x]÷[(x²-1)分之(x+1)+1],其中x=根号2+1先化简,再求值:[(x²-2x+1)分之x]÷[(x²-1)

先化简,再求值:[(x²-2x+1)分之x]÷[(x²-1)分之(x+1)+1],其中x=根号2+1
先化简,再求值:[(x²-2x+1)分之x]÷[(x²-1)分之(x+1)+1],其中x=根号2+1

先化简,再求值:[(x²-2x+1)分之x]÷[(x²-1)分之(x+1)+1],其中x=根号2+1

:[(x²-2x+1)分之x]÷[(x²-1)分之(x+1)+1],其中x=根号2+1
=[x/(x-1)²]÷[(x+1)/(x-1)(x+1)+1]
=[x/(x-1)²]÷[1/(x-1)+1]
=[x/(x-1)²]÷[(1+x-1)/(x-1)]
=[x/(x-1)²]÷[x/(x-1)]
=1/(x-1)
=1/(√2+1-1)
=1/(√2)
=(√2)/2